MATERIAL BANGUNAN RUMAH TINGGAL SEBAGAI KETAHANAN RESIKO COVID-19: STUDI KASUS RUMAH TINGGAL DI KECAMATAN MENGANTI, KABUPATEN GRESIK, JAWA TIMUR - Heristama Anugerah Putra; Oktafiana, Brina (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2023)
Health protocols must continue to be implemented in preventing the Covid-19 virus even though conditions in Indonesia currently show a reduced rate of spread and infection. This is because the government has implemented a mass vaccination process for all Indonesian citizens. Moreover, PKKM status has been abolished and gives residents freedom to do their activities inside or outside the room. The main objective of this study is to investigate the impact of material selection on passive cooling in residential buildings in response to the risk of Covid-19. The comfort level of occupants when they are inside the house can be determined from the use of residential materials in this Gresik Regency. The identification process uses the method of quantitative heat transfer comparison technique of each building material in several areas of residential buildings. The process of identifying existing materials in buildings against plans for the use of materials in the residential redesign process. Achievement of durability here is the accuracy of placement and selection as well as the characteristics of the materials used. Conduction and radiation processes are contributing factors to the heat distribution process in buildings. Thermal comfort is greatly influenced by the use of materials compared to the rate of air exchange. The heat transfer value can be of great value if the material used has a U-value and a large surface area and this causes the level of thermal comfort in the building to be low.